PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION (STUDI PADA PERAWAT RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU) - Teguh Harian Syah; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much influence organizational culture and organizational commitment to turnover intention. The sample in this study was taken as many as 56 respondents and the measurement technique used was simple random sampling technique. The data in this study used a survey through questionnaires diidi by employees. Data obtained using simple regression analysis and multiple regression analysis. The results of this study indicate that organizational culture has a significant negative effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention. And simultaneously organizational culture and organizational commitment have a significant effect on turnover intention. Further researchers are advised to use other methods in researching turnover intention, for example through in-depth interviews with respondents.  Keywords: Organizational Culture, Organizational Commitment and Turnover intention